The Impact of Sustainable Social Entrepreneurship on Economic Inclusivity in Rural Areas in Indonesia - Effendi, Darwan; Lestari, Fitri; Gabrienda, Gracia (Westscience Press, 2025)
This study investigates the impact of sustainable social entrepreneurship on economic inclusivity in rural areas of Indonesia, using a quantitative analysis with 125 respondents and data processed through Structural Equation Modeling - Partial Least Squares (SEM-PLS). The findings reveal that sustainable social entrepreneurship significantly influences economic inclusivity through key factors, including access to resources, equitable opportunities, participation in economic activities, and income distribution. The model explains 68% of the variance in economic inclusivity, indicating strong predictive power. These results emphasize the transformative potential of social entrepreneurship in addressing socio-economic disparities and fostering equitable growth in rural Indonesia. The study contributes to the theoretical understanding of inclusive development and provides actionable insights for policymakers and practitioners aiming to promote sustainable rural economies.